Zasady rolniczej rekultywacji gruntów pogórniczych = The principles agricultural recultivation of dump soils - Gilewska, Mirosława (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the confrontation of legal acts and achieved reclamation results it can be said that reclamation is a set of engineering and agrotechnic proeedures as well as biogeochemic proeesses which create new biocenotic structure of industrial soil.
Keywords: 2 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zagospodarowanie zlewni" (21-22.06.2001)